Integrated provenance analysis of Carboniferous deposits from Northeastern Siberia: Implication for the late Paleozoic history of the Arctic. (1st September 2015) - Ershova, Victoria B.; Prokopiev, Andrei V.; Khudoley, Andrey K.
Highlights: Our data reveal a major shift in provenance occurred in the Late Visean. The Lower Visean clastic rocks were only derived from a Siberian basement and its sedimentary cover. Late Visean-Upper Carboniferous clastics are derived from non-Siberian sources. This data suggests an earlier than previously assumed collision between Kara terrane and Siberia. Existence of two major fluvial systems draining the Siberia during the Carboniferous. Abstract: An integrated provenance analysis based on sandstone petrography, distribution of REE and trace elements, and U/Pb detrital zircon dating of Carboniferous sedimentary rocks of northern Verkhoyansk Fold and Thrust Belt (FTB) provides new insights into the tectonic evolution of NE Siberia. According to petrographic and geochemical data, Lower Visean sandstones had local provenance that contained mafic magmatic rocks. Wide distribution of ca. 2075 Ma detrital zircons known in the basement of neighboring Olenek and Ust'-Lena uplifts supports local provenance of the Lower Visean sandstones. Starting from Late Visean, clastic sediments have geochemical and petrographic compositions that are characteristic for erosion predominantly felsic rocks in a more remote source region. Detrital zircon age distributions in the Upper Visean – Upper Carboniferous sandstones, point to Taymyr – Severnaya Zemlya FTB and Central Asian Orogenic Belt (CAOB) as the most likely provenances for clastic rocks. However, wide distribution of Neoproterozoic and early Paleozoic detrital zircons that are not typical for synchronous CAOB-derived clastic rocks in the West Verkhoyansk, provide evidence for other than CAOB source area. We infer that the most likely source for Neoproterozoic – early Paleozoic detrital zircons in the Upper Visean – Upper Carboniferous sandstones is the Taimyr-Severnaya Zemlya FTB. The shift to sources from the Taimyr-Severnaya Zemlya FTB suggests an earlier (Late Visean) age for the collision between Kara terrane and Siberia than has been previously assumed (Late Carboniferous – Permian). Our paleogeographic restoration reveals the existence of two major fluvial systems draining eastward across the Siberian Craton during the Carboniferous: the Paleo-Lena in the south and the Paleo-Khatanga in the north.